Factors Affecting Impulse Buying on Online Shopping amongst Youth: A Structural Equation Modeling Approach (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article aims to identify the constructs that impacts impulse buying on online shopping amongst youth. The research was conducted based on the response received from 301 responses from the youth population.  The main significant components consist of scarcity, serendipity, e-commerce, social shopping, value shopping and relaxation shopping. Factors were identified from literature survey and exploratory factor analysis was utilized for grouping the variables   under different components. The findings contributed that the six latent variables are significant contributors to the affective impulse buying tendency. This was validated using structural equation modeling approach utilizing AMOS 22.0. This research helps to understand the rising trend of e-commerce in the developing country’s prospective.  It also develops a foundation for future research and significant insights to perceive the impulse buying on online shopping amongst youth.